Porcine bile acids promote the utilization of fat and vitamin A under low-fat diets - Yang, Bowen; Huang, Shimeng; Yang, Ning; Cao, Aizhi; Zhao, Lihong; Zhang, Jianyun; Zhao, Guoxian; Ma, Qiugang (Frontiers in Nutrition, 2022)
Fat-soluble vitamin malabsorption may occur due to low dietary fat content, even in the presence of an adequate supply of fat-soluble vitamins. Bile acids (BAs) have been confirmed as emulsifiers to promote fat absorption in high-fat diets. However, there are no direct evidence of exogenous BAs promoting the utilization of fat-soluble vitamins associated with fat absorption in vitro and in vivo. Therefore, we chose laying hens as model animals, as their diet usually does not contain much fat, to expand the study of BAs. BAs were investigated in vitro for emulsification, simulated intestinal digestion, and release rate of fat-soluble vitamins. Subsequently, a total of 450 healthy 45-week-old Hy-Line Grey laying hens were chosen for an 84-day feeding trial. They were divided into five treatments, feeding diets supplemented with 0, 30, 60, 90, and 120 mg/kg BAs, respectively. No extra fat was added to the basic diet (crude fat was 3.23%). In vitro, BAs effectively emulsified the water-oil interface. Moreover, BAs promoted the hydrolysis of fat by lipase to release more fatty acids. Although BAs increased the release rates of vitamins A, D, and E from vegetable oils, BAs improved for the digestion of vitamin A more effectively. Dietary supplementation of 60 mg/kg BAs in laying hens markedly improved the laying performance. The total number of follicles in ovaries increased in 30 and 60 mg/kg BAs groups. Both the crude fat and total energy utilization rates of BAs groups were improved. Lipase and lipoprotein lipase activities were enhanced in the small intestine in 60, 90, and 120 mg/kg BAs groups. Furthermore, we observed an increase in vitamin A content in the liver and serum of laying hens in the 60, 90, and 120 mg/kg BAs groups. The serum IgA content in the 90 and 120 mg/kg BAs groups was significantly improved. A decrease in serum malondialdehyde levels and an increase in glutathione peroxidase activity were also observed in BAs groups. The present study concluded that BAs promoted the absorption of vitamin A by promoting the absorption of fat even under low-fat diets, thereupon improving the reproduction and health of model animals.